Cultural distortion risk and tourist loyalty at silk road heritage: The mediating roles of perceived value and satisfaction - Kejun Wu; Lihui Su; Sen Zhang; Shuanyan Yang; Aoxue Xing; Jingbo Zhou (PLoS ONE, 2025)
As the core carrier of cross-cultural communication, World Cultural Heritage sites along the Silk Road face challenges from cultural distortion risk. However, the specific mechanisms linking this risk to tourist loyalty, particularly the mediating roles of perceived value and satisfaction, remain under explored. This study aims to elucidate this dynamic pathway by constructing and testing a theoretical model of “cultural distortion risk→Perceived Value→Tourist Satisfaction→Tourist loyalty “. Focusing on the Maijishan Grottoes and utilizing 381 valid questionnaires, we employed covariance-based structural equation model (CB-SEM) grounded in Knowledge-Attitude-Practice (KAP) theory and the Stimulus–Organism–Response (SOR) model reveal the chain effects of cultural distortion risk on tourists’ cognition, emotions, and loyalty. These results demonstrate: (1) cultural distortion risk significantly reduces perceived value (β = −0.409, p < 0.001), while enhancing authenticity boosts value assessment, (2) perceived value and satisfaction act as significant chain mediators between cultural distortion risk and loyalty (β = −0.397, p < 0.001), and (3) perceived value alone does not directly predict loyalty, suggesting emotional responses (satisfaction) are crucial in loyalty decisions. The study underscores the importance of cultural promotion and enhancing tourists’ cultural perception to foster satisfaction and loyalty. These findings contribute significantly to the theoretical understanding of risk perception and behavioral responses in global cultural heritage tourism, particularly by empirically validating a chain mediation mechanism. They also offer concrete, evidence-based strategies for heritage site managers to mitigate cultural distortion and enhance tourist revisit intentions.